2013
DOI: 10.1016/j.chiabu.2012.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Gender specific association of child abuse and adult cardiovascular disease in a sample of patients with Basal Cell Carcinoma

Abstract: Objective The aim of this study is to examine whether child abuse or neglect is more strongly associated with adult cardiovascular disease, and whether these associations differ by gender. Methods A total of 116 participants (mean age 57.75 years) reported their experience of childhood maltreatment using the well-validated Childhood Experience of Care and Abuse Questionnaire. Cardiovascular disease was assessed using the Older Adults Resources Survey Multidimensional Functional Assessment Questionnaire. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
(60 reference statements)
0
17
1
Order By: Relevance
“…Less evidence exists for associations with psychosocial adversity in childhood. Previous studies have reported associations between specific types of psychosocial adversity in childhood and increased CVD risk;(Gooding et al, 2016; Hosang et al, 2013; Rich-Edwards et al, 2012; Thurston et al, 2014) particularly sexual and physical abuse. Very few studies have assessed associations of cumulative psychosocial adversity in childhood with multiple CVD risk factors in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less evidence exists for associations with psychosocial adversity in childhood. Previous studies have reported associations between specific types of psychosocial adversity in childhood and increased CVD risk;(Gooding et al, 2016; Hosang et al, 2013; Rich-Edwards et al, 2012; Thurston et al, 2014) particularly sexual and physical abuse. Very few studies have assessed associations of cumulative psychosocial adversity in childhood with multiple CVD risk factors in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…low head of household social class, household overcrowding and low parental education) is associated with cardiovascular disease (CVD) risk factors in adulthood (Galobardes, Smith, & Lynch, 2006; Havranek et al, 2015). However, there is much less evidence for associations of psychosocial adversity in childhood (for example, sexual abuse and physical neglect) with later CVD risk, and existing studies have reported both positive and null findings (Crowell et al, 2015; Gooding et al, 2016; Halonen et al, 2015; Hosang et al, 2013; Rich-Edwards et al, 2012; Su et al, 2015; Thurston et al, 2014). The Adverse Childhood Experiences (ACE) study has been pivotal in characterising medium and long-term health outcomes of psychosocial adversity in childhood and Felitti et al have previously reported a strong graded relationship between the number of categories of retrospectively reported adverse childhood exposures and the presence of CVD (including ischemic heart disease) in a study of 9508 adults (Felitti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not have data on other potentially confounding factors such as childhood adversity. For example, individuals who have experienced childhood abuse, especially women, are more likely to have less adaptive intimate interactions and be at risk for cardiovascular disease (4244). …”
Section: Discussionmentioning
confidence: 99%
“…Childhood adversity is a non-specific risk factor and has been linked to other emotional problems [18], psychiatric illnesses [16,19,20] and physical disorders [21,22]. A better understanding of the specific mechanisms that underlie the childhood adversity/depression association is needed.…”
Section: Childhood Adversitymentioning
confidence: 99%